CHOP Plus Sequential Mogamulizumab As First-Line Therapy for Untreated Adult T-Cell Leukemia-Lymphoma - Tanimoto, Kazuki; Kato, Koji; Aoki, Takatoshi; Yoshimoto, Goichi; Choi, Ilseung; Kadowaki, Masanori; Sugio, Yasuhiro; Kuriyama, Takuro; Kawano, Noriaki; Suzuki, Ritsuro; Miyawaki, Kohta; Henzan, Hideho; et al. (Blood, 2021)
Introduction: Adult T-cell leukemia/lymphoma (ATL) is an aggressive peripheral T-cell lymphoma caused by human T-cell lymphotropic virus type I. In younger patients, allogeneic hematopoietic stem cell transplantation (HSCT) has been shown to improve prognosis through a graft-versus-ATL (GvATL) effect. On the other hand, elderly patients with ATL are often not amenable to HSCT, and the prognosis is extremely poor with existing chemotherapy. The most widely used chemotherapy for ATL, CHOP (combination of cyclophosphamide-doxorubicin-vincristine-prednisone) and similar chemotherapy, have shown a complete response (CR) rate of about 20% and a long-term prognosis of less than 10%. In a phase II study of mogamulizumab, a humanized defucosylated anti-C-C chemokine receptor 4 monoclonal antibody, in concurrent combination with chemotherapy (mLSG15), the primary endpoint of CR was 52% in the mLSG15 + mogamulizumab group compared to 33% in the mLSG15 alone group. However, no improvement was observed in overall survival (OS) or progression-free survival (PFS). In addition, mLSG15 is a potent chemotherapy and not feasible in majority of elderly patients. Considering the possibility that mogamulizumab may unlock the tumor immune evasion mechanism by removing regulatory T cells and exert an immunological effect like GvATL, we investigated its usefulness as an immunological consolidation therapy following chemotherapy, with the aim of suppressing recurrence. Methods: New-onset treatment-naive ATL patients who were not eligible to HSCT received 3 courses of CHOP (combination of cyclophosphamide div 750 mg/m 2/day1, doxorubicin iv 50 mg/m 2/day1, vincristine iv 1.4 mg/m 2/day1 [max. 2.0 mg/body, and prednisone po/iv 100 mg/body/day1-5) at 21-day intervals, and then the first course of mogamulizumab (1 mg/kg for 8 doses at 2-week intervals) was initiated between the start of the third course of CHOP-21 and day 42. The primary endpoint was OS at months 12. Secondary endpoints were proportion of subjects with PFS, OS, overall response rate (ORR), organ-specific response rate, CR rate and adverse events (AEs) at month 12. Results: A total of 24 patients were enrolled and the median age was 75.5 years (range, 64-85). The median follow-up period was 11.0 (3.0-30.6) months. Five subjects discontinued study treatment before mogamulizumab administration attributable to insufficient effect (n=2), continuation deemed inappropriate (n=2), and start of the next course extended (n=1). ORR was 87.5%. Organ-specific response rates for peripheral blood, other than peripheral blood, target lesion, and skin lesion were 83.3%, 87.5%, 79.2%, and 66.7%, respectively. OS and PFS rates in the full analysis set (FAS) at months 12 were 52.6 (30.9-70.4)% and 26.6 (10.9-45.3)%, respectively. The median survival time (MST) and 80% confidence interval (CI) for OS was 12.1 (5.0 -21 .0) months (Figure 1). Since the lower limit of the 80% CI was below the threshold of 6 months, this treatment was not considered to be effective. However, the point estimate of MST was 12.1 months, which was equivalent to the expected value. One possible reason for the failure to reach statistical significance could be attributable to occurrence of events in the early stage of the protocol regimen. In other words, patients who did not respond to the preceding chemotherapy did not benefit from mogamulizumab, and only patients who managed to overcome chemotherapy benefited from the immune effects of mogamulizumab, resulting in long-term survival (Figure 1). In the long-term follow-up, the MST (95% CI) of the FAS was 12.4 (4.9-21.0) months, and the median OS (95% CI) at 24 months was 25.1 (9.6-44.1) %. AEs were observed in 16 subjects, of which serious AEs (grade 4/5) were observed in 5 subjects (acute respiratory distress syndrome, ventricular fibrillation, heart failure, hyponatremia, and pneumonia). Largely, AEs were resolved/recovered in 14 subjects including 3 subjects with serious AE; 2 subjects resulted in death, which were not considered treatment-related. Conclusions: Mogamulizumab as an immunological consolidation therapy after CHOP 21 might be one of the treatment options for transplant-ineligible elderly patients with previously-untreated ATL, despite not clearly showing improved OS. Further studies are warranted to examine the dosing timing of mogamulizumab to obtain its maximum benefit for prolonged survival. [Display omitted] Kato: Abbvie: Consultancy, Research Funding; AstraZeneca: Consultancy; Bristol-Myers Squibb: Honoraria, Research Funding; Celgene: Consultancy, Honoraria, Research Funding; Chugai: Consultancy, Honoraria, Research Funding; Daiichi Sankyo: Consultancy, Research Funding; Dainippon-Sumitomo: Honoraria; Eisai: Consultancy, Research Funding; Janssen: Consultancy, Honoraria, Research Funding; Kyowa Kirin: Honoraria, Research Funding; MSD: Honoraria; Mundi: Honoraria; Novartis: Consultancy, Research Funding; Ono: Honoraria, Research Funding. Suzuki: Kyowa-kirin: Honoraria, Research Funding, Speakers Bureau; Chugai: Honoraria, Research Funding, Speakers Bureau; Taiho: Research Funding; Ohtsuka: Honoraria, Research Funding; Takeda: Research Funding, Speakers Bureau; Shionogi: Research Funding; Eisai: Honoraria, Research Funding; Bristol-Meyer Squib: Honoraria; MSD: Honoraria; Janssen: Honoraria; Abbvie: Speakers Bureau; Meiji Seika: Honoraria, Speakers Bureau; Ohtsuka: Honoraria. Akashi: Sumitomo Dainippon Pharma: Consultancy; Kyowa Kirin: Consultancy, Research Funding; Celgene: Research Funding; Astellas Pharma: Research Funding; Shionogi: Research Funding; Asahi Kasei Pharma: Research Funding; Chugai: Research Funding; Bristol-Myers Squibb: Research Funding.